Trust, discretion and responsibility : the division of technical labour - MacGovern, Patrick [Verfasser] (My University, 1996)
"This paper examines the role which multinational corporation (MNC) branch plants play in the development and maintenance of the boundaries between technical occupations in the Irish Republic. In doing so, it examines recent attempts to characterise such workers as incumbents of 'high-discretion high trust' work roles and also as 'trusted workers'. This paper argues that such attempts are lacking in explanatory power because they fail to account for other factors. In the Irish case, these include levels of qualification, the higher status of theoretical and abstract knowledge, the fusion of technical and managerial functions and the greater organisational importance of the more senior technical positions." (author's abstract, IAB-Doku) ((en)) Der Beitrag befasst sich mit den Arbeitsanforderungen in technischen Berufen und der daraus resultierenden Arbeitsteilung. Dies wird am Beispiel von multinationalen Unternehmen in Irland untersucht. Anhand von qualitativen Interviews wird die Bedeutung von Qualifikation, theoretischem Wissen und Führungstätigkeiten erhoben. (IAB)
Keywords: G 2.3.1 Arbeitsteilung & -organisation; G 2.3 Wandel von Arbeit & Wirtschaft; G 2.4 Sozialer Wandel; I 2.3.4 Asien; Techniker; Arbeitsteilung; Arbeitsanforderungen; Verantwortung; Berufsrolle; Personalgewinnung; Qualifikationsanforderung; Führungskraft; Irland